Resilience in sudden changes and crises related to micro-entrepreneurship - Forsten-Astikainen, R. (Riitta); Muhos, M. (Matti) (Academic Conferences and Publishing International, 2018)
Abstract The paper examines micro-entrepreneurs’ resilience to significant changes in a company. The focus of this research is on uncovering the kinds of changes and crises entrepreneurs met and on how to classify these changes and crises? The unexpected changes that entrepreneurs may face can have a significant impact on both their current and future activities and can be directed either at the individual or the business level. In micro-entrepreneurship, entrepreneurs typically have to address changes and crises alone. To a micro-entrepreneur, a sudden change can be challenging because he/she does not necessarily have a support network to provide useful or sufficient help (Alonso et al., 2015). Managing such situations requires resilience and flexibility from entrepreneurs and companies alike. This empirical research was qualitative by nature and the research method was a retrospective multiple case study. The data collection method was based on semi-structured thematic interviews with 12 entrepreneurs and managers from the social and health care sector in Northern Finland. All interviews were audio-recorded and transcribed. The transcriptions were analysed by content analysis with an interpretative approach, each on a case-by-case basis. The data were processed using qualitative data analysis software. Preliminary results suggested that the challenges that micro-entrepreneurs considered the most serious related to internal and external interventions, such as problems with staff, management, management models, authorities, institutions and bureaucracy. In addition, emotional interventions like one’s own wellbeing and a lack of guidance and support related to real crises is a reality of a micro-entrepreneur’s life.